Development of a Scale to Assess Immigrant Women's Needs for Pregnancy and Postpartum Adaptation - Kyung Won Kim; Geum Hee Jeong (Korean Society of Women Health Nursing, 2013)
PURPOSE: The purpose of this study was to develop a scale to assess immigrant women's needs for pregnancy and postpartum adaptation and to test the reliability and validity of the scale. METHODS: To construct scale items, critical issues and difficulties associated with pregnancy and postpartum adaptation of immigrant women were identified and categorized through a literature review. Fifty-two scale items were constructed, and data for validity and reliability testing was collected with a questionnaire survey from 367 immigrant women. Data were analyzed with descriptive statistics, factor analysis, and reliability coefficients. RESULTS: The final measurement scale to assess immigrant women's pregnancy and postpartum adaptation consisted of 48 items and 7 factors (adaptation to daily activity during pregnancy, cross-cultural understanding and personal respect, understanding of the process of pregnancy and delivery, baby rearing and family support, physical and emotional adaptation after childbirth, nutrition during pregnancy, and sexual life adaptation). The seven factors accounted for 64.26% of the variance, and Cronbach's alpha was .96. CONCLUSION: The scale developed by this study is a reliable and valid instrument and can be used to assess needs of pregnancy and postpartum adaptation and can be utilized in providing nursing interventions for immigrant women.